The utilization of the TE-LA application to improve report text writing skills for grade viii students of Muhammadiyah Junior High School Malang - Setiawan, Arif; Hiu, Ho Ngoc; Hima, Anindha Nidhomil; Fauzan, Fauzan (BAHASTRA, 2024)
Writing report texts in Indonesian learning is an interesting object of study to be researched. This is due to the lack of students' knowledge about how to write report texts, so they need an application that can help and make it easier for students to write report texts. This study aims to evaluate the effectiveness of the TE-LA application as a learning medium in improving report text writing skills for grade VIII students of Muhammadiyah Malang Junior High School. This study uses a descriptive percentage method. The population and sample in this study are grade VIII students of SMP Muhammadiyah 6 Dau Malang, SMP Muhammadiyah 4 Singosari, SMP Muhammadiyah 10 Turen, and SMP Muhammadiyah 1 Malang. A total of 40 students from the four Junior High Schools (SMP) were used as research samples, which were taken using a simple random sampling technique.The data collection technique uses interviews and questionnaires. The data analysis technique used is descriptive analysis. The results of the study show that the questionnaire that has been distributed has received a good response with a percentage of 70% which is in the good category and the existence of the TE-LA Application (Report Text) can also play a role as a learning medium that can provide benefits for students. The results of this research can make an important contribution to the development of technology-based learning media, especially the TE-LA application as a tool for writing skills.